2021
DOI: 10.1111/hel.12867
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacterspecies binding to the human gastric mucosa

Abstract: Helicobacter pylori infects half of the world population, being associated with several gastric disorders, such as chronic gastritis and gastric carcinoma. The Helicobacter genus also includes other gastric helicobacters, such as H. heilmannii¸ H. ailurogastricus, H. suis, H. felis, H. bizzozeronii, and H. salomonis. These gastric helicobacters colonize both the human and animal stomach. The prevalence of gastric non-Helicobacter pylori Helicobacter (NHPH) species in humans has been described as low, and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…6,21,22 Although H. suis colonizes the hog stomach and is the source of zoonotic infection in a high percentage of human cases of H. suis infection, [23][24][25] the infection rate among hog farmers is not higher than that of individuals who have no contact with animals. 26,27 It has been hypothesized that H. suis infects humans via the consumption of contaminated pork. 28,29 However, there is no clear evidence regarding the H. suis infection route or period.…”
Section: Discussionmentioning
confidence: 99%
“…6,21,22 Although H. suis colonizes the hog stomach and is the source of zoonotic infection in a high percentage of human cases of H. suis infection, [23][24][25] the infection rate among hog farmers is not higher than that of individuals who have no contact with animals. 26,27 It has been hypothesized that H. suis infects humans via the consumption of contaminated pork. 28,29 However, there is no clear evidence regarding the H. suis infection route or period.…”
Section: Discussionmentioning
confidence: 99%
“…Laser confocal fluorescence microscopy (Leica TCS SP8, Germany) was used for cell imaging. 1 H NMR and 13 C NMR spectra were recorded on Bruker Advance Spectrometer (Bruker, Germany). High-resolution mass spectra (HRMS) were obtained on a Varian 7.0 spectrometer with ESI.…”
Section: Methodsmentioning
confidence: 99%
“…Helicobacter pylori ( H. pylori ) has infected more than 50% of the population worldwide and has been a significant threat to human health. [ 1 ] Clinical therapy to eradicate H. pylori usually contains two antibiotics (clarithromycin + amoxicillin or metronidazole) and one proton pump inhibitor. [ 2 ] In the last few decades, however, the abuse of antibiotics has led to increased H. pylori resistance to antibiotics and remarkably reduced the treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…HFD induction reduced the proportion of Lactobacillus and Bacteroidetes while K. marxianus JLU-1016 and AR strain JLU-1016A treatments reversed the reduction in these genera (Figure 10(i)). Many novel Helicobacter have been identified with human in many Cellular Microbiology infection diseases [35][36][37] and are increased in the HG, and the genera were inhibited after K. marxianus JLU-1016 and AR strain JLU-1016A treatments (Figure 10(i)). Function analysis showed that HFD induction reduced the levels of the protein involved with multiple sugar transport system, polar amino acid transport system, and peptide transport system and increased the protein involved with antibiotic transport system, beta-galactosidase, and iron complex outermembrane receptor while K. marxianus and the AR strain reversed all these parameters (Figure 10(j)).…”
Section: K Marxianus Reduced the Apoptotic Rate In Hfd-mentioning
confidence: 99%